Delineating Plasmodium liver infection across space and time. Issue 2 (February 2023) - Hildebrandt, Franziska; Ankarklev, Johan; Matuschewski, Kai
Abstract: The liver is a major entry point and gatekeeper for invasive pathogens. However, high-resolution, spatiotemporal transcriptomic analysis of host–pathogen interactions has remained challenging. Afriat et al . have deconvoluted Plasmodium berghei liver-stage maturation at an unprecedented scale and discovered molecular signatures of heterogeneity during pre-erythrocytic development of malarial parasites.